Post‐fire ductility of reinforcing steel. Issue 2 (1st September 2021) - Lapuebla‐Ferri, Andrés; Pons, David; Romero, Manuel L.
Abstract: In this work, the post‐fire ductility of steel reinforcements in reinforced concrete structures was studied experimentally. Specimens were subjected simultaneously to a constant tensile load and a heating up to a target temperature, which was a percentage of the 'critical temperature' for the load level applied. After that, the specimen was left to cool to room temperature and submitted to tensile testing in order to evaluate its residual ductility. Critical temperatures for each load level tested were obtained by performing transient‐state tests. In addition, unloaded specimens were subjected to the same thermal cycle of heating and cooling for comparison purposes. Results indicated that the residual ductility of a reinforcement depends on the maximum temperature reached and the load level it was bearing during the heating and cooling thermal cycle. It was demonstrated that ductility properties were not always recovered after cooling down, and the current code requirements for the ductility class of a reinforcement bar were not fulfilled. The obtained information can be relevant when deciding on the eventual reinstatement of a reinforced concrete structure in a post‐fire scenario.